Comparative Ecosystem Benefits of Common Urban Trees and Palms in South Florida - Marguerite Beckford; Gary W. Knox (EDIS)
This new 2-page factsheet was written to support urban forestry Extension clientele queries for information guiding Florida HOA and property owner decisions on whether to replace hardwood trees with palms, due to palms’ compact growth habit and lower leaf-shed volume, compared to hardwood trees. Written by Marguerite Beckford and Gary W. Knox, and published by the UF/IFAS Environmental Horticulture Department.